Validation of football's velocity provided by a radio-based tracking system - Seidl, T.; Czyz, T.; Spandler, D.; Franke, N.; Lochmann, M. (Procedia Engineering, 2016)
Nowadays, many tracking systems in football provide positional data of players but only a few systems provide reliable data of the ball itself. The tracking quality of many available systems suffers from high ball velocities of up to 34 ms-1 and from the occlusion of both the players and the ball. Knowledge about the position and velocity of the football can yield valuable information for players, coaches and the media.